Reducing vibrations of the fan-electric motor system on the example of a renovated ventilation installation – a case study - Walaszczyk, Juliusz (Instal, 2024)
In recent years, less and less attention has been paid to elements related to the proper depreciation of rotating machines (fan – electric motor, pump – electric motor, etc.). In the pursuit of reductions, especially in investment costs, hasty decisions are often made related to “slimming” support frames or foundations for rotating machines. To illustrate the effects of such actions, the article presents and discusses the results of vibration measurements performed in a real facility before and after replacing the ventilation installation that serves an industrial hall. The measurement results were compared with the results of calculations made based on 3 theoretical methods. It has been shown that the appropriate mass of the support frame and careful levelling of the systems have a decisive impact on the vibration amplitudes obtained. This thesis was proven by reducing vibrations from 16.39 mm/s RMS to 4.23 mm/s RMS. It has been shown that by regular monitoring of isolators depreciation one can effectively and quickly detect problems related to the operation of fans and electric motors (damage to bearings, dangerous vibration amplitudes of building partitions).
Keywords: vibrations; vibration isolators; centrifugal machines; ventilation; HVAC